Estimation of Hepatic Elasticity by Shear Wave Sonoelastography among Asymptomatic Individuals in a Tertiary Level Hospital - Maharjan, Santosh; Lohani, Benu; kayastha, Prakash; Suwal, Sundar; Paudel, Sharma (Journal of Nepal Health Research Council, 2021)
Background: Shear wave elastography is currently most widely used method for determining the elasticity of liver. Liver fibrosis, final common pathway of chronic liver disease, is associated with increased liver stiffness. This study aimed to obtain normal liver elasticity in Nepalese population, as it can be used as reference in future for determination of elasticity in abnormal liver.Methods: Quantitative prospective study was done in 132 individuals with normal liver function tests. Shear wave elastography was done to measure elasticity of both lobes of liver and thus obtained values were also correlated with age, gender and fatty changes in liver.Results: Forty seven out of 132 individuals had fatty liver. Mean elasticity of liver was 4.40±0.60 kPa with range of 3.12-6.62 kPa. There was no significant difference between mean elasticity of right and left lobe of liver. No significant correlation was found between mean liver elasticity with age and gender. There was statistically significant difference in the mean elasticity between non-fatty and fatty liver (p=0.041).Conclusions: The study established normal elasticity of liver in Nepalese population and this reference can be used to obtain abnormal liver elasticities. Keywords: Elasticity; normal liver; shear wave